ANALISIS JENDER WACANA MATERI PELAJARAN BUKU TEKS BAHASA INDONESIA DI SD KELAS TINGGI BENGKULU SELATAN - S, Eva (UNIB Press, 2015)
The research purpose to express stereotype women form and stereotype man form which constituante from jender, and equivalent jender form in text book Indonesian SD (elementary school). The text book selection as detailed examination object is text book Indonesian elementary school are purpose in elementary school high class South Bengkulu erlangga edition study 2010-2011 years. Speaking in text book are thorough beginning from four, five and six class. The research used analysis contents program. Analysis data involue the use of analysis data used. Analysis contents technic. Based on draft analysis sentence the thing which contains stereotype woman (SW), stereotype man (SP) and equivalent jender (KJ) interior discourse in text book it is sentence which give code apart. Equivalent form jender in the sentence in discourse text book Indonesia Language at elementary school high class Bengkulu South explain about equivalent character between woman and man in domestic zone and public which is not yet many get in four, five and six class, until book mentionet not yet equivalent jender. Based on result research can suggestion which is relation with necessarry text book which is give insight equivalent jender. In addition to needed sees jender in arranging curriculum Indonesia Language elementary school.